Análisis de la comercialización del cacao y su influencia en los productores de la parroquia Los Ángeles del cantón Ventanas - Viscarra Salazar, Luis Miguel (2020)
A detailed study of small cocoa producers was carried out through surveys in the Los Angeles parish of the Ventanas canton of the Los Ríos province in order to update the information on the production and marketing of the item and establish the effect it has on the same. It was analyzed based on parameters such as planted area, type of cocoa planted, time as a cocoa producer, belongs to some producer organization, has financing, how the product is sold (slime or dried), sells at market price, has a fixed market and the opinion of the producer about the problems they currently have in marketing, among others. The results are alarming in terms of the current situation of the small cocoa producer in the area, which is practically totally abandoned by government entities in agricultural matters and that it is urgent to take this situation into account, the marketing chains are in In the hands of the intermediaries who are the ones who finely take the product to its final destination, the commercialization systems used are very traditional; they make them lack improvements in the sales of their products and therefore their profitability is affected. All this leads to the search for government support through entities such as the MAG that would be in charge of advising on the management of the crop and its marketing systems, the Universities with the link projects that help form a framed association to seek new markets without the need for intermediaries and finally the state financing entities such as BanEcuador that would be in charge of providing long-term credits.